Association between the morphological and productive characteristics in the selection of elephant grass clones Associação entre características morfológicas e produtivas na seleção de clones de capim-elefante - Márcio Vieira da Cunha; Mario de Andrade Lira; Mércia Virginia Ferreira dos Santos; Erinaldo Viana de Freitas; José Carlos Batista Dubeux Junior; Alexandre Carneiro Leão de Mello; Kalina Gerciane Rodovalho Martins (Revista Brasileira de Zootecnia, 2011)
The objectives in this work were to study the association between the morphological and productive characteristics in Pennisetum sp. clones, and to identify the morphological characteristics responsible for the productivity in Pennisetum cp. clones. The canonical correlations were evaluated and the path analysis was made from the simple genotypic correlation matrix between the morphological and productive characteristics of eight Pennisetum sp. clones (Taiwan A-146 2.37, Taiwan A-146 2.27, Taiwan-146 2.114, Merker México MX 6.31, Mott, HV-241, Elefante B and IRI-381). The canonical correlations were significant at 1% probability by the Chi-square test. The first pair of canonic factors, with correlation of 0.9999, related the plants with the highest dry matter content to plants with lower leaf area indexes, light perception and leaf angle. The second pair of canonic factors, with correlation of 0.9999, related the plants with the highest dry matter production to the plants with higher basal tiller density, height, and low green leaf number per tiller. The results of the path analysis indicated that the light interception is determinant in dry matter content expression of Pennisetum sp. clones, while the basal tiller density and plant height are responsible for dry matter production in these clones. Os objetivos neste trabalho foram estudar a associação entre características morfológicas e produtivas em clones de Pennisetum sp. e identificar as características morfológicas responsáveis pela produtividade em clones de Pennisetum sp. Foram avaliadas as correlações canônicas e feita análise de trilha a partir da matriz de correlações genotípicas simples entre características morfológicas e produtivas de oito clones de Pennisetum sp. (Taiwan A-146 2.37, Taiwan A-146 2.27, Taiwan-146 2.114, Merker México MX 6.31, Mott, HV-241, Elefante B e IRI-381). As correlações canônicas foram significativas a 1% de probabilidade pelo teste do qui-quadrado. O primeiro par de fatores canônicos, com correlação de 0,9999, associou plantas com maior teor de matéria seca a plantas com menores índices de área foliar, interceptação luminosa e ângulo foliar. O segundo par de fatores canônicos, com correlação de 0,9999, associou plantas com maior produção de matéria seca a plantas com maior densidade de perfilhos basais, altura, e menor número de folhas verdes por perfilho. Os resultados da análise de trilha indicaram que a interceptação luminosa é determinante na expressão do teor de matéria seca de clones de Pennisetum sp., enquanto a densidade de perfilhos basais e a altura da planta são responsáveis pela produção de matéria seca nesses clones.